2013
DOI: 10.4103/2231-0770.118465
|View full text |Cite
|
Sign up to set email alerts
|

Uterine leiomyoma with spontaneous intraleiomyoma hemorrhage, perforation, and hemoperitoneum in postmenopausal woman: Computed tomography diagnosis

Abstract: Spontaneous intraleiomyoma hemorrhage, perforation, and hemoperitoneum are very rare complications of uterine leiomyoma. We report a case of postmenopausal woman who presented with acute abdomen found to have intraleiomyoma hemorrhage, perforation, and hemoperitoneum. Our case also illustrates the computed tomography findings of such complications of uterine leiomyoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, Salehi et al [31] reported a case of a 15-year-old adolescent with a 9.5/8.4/10.7 cm heterogeneous, hypoattenuating, symptomatic solid adnexal mass that resulted in being a degenerative uterine leiomyoma. Several other cases in the puerperal period, in perimenopause or even in postmenopause have been reported [18,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Salehi et al [31] reported a case of a 15-year-old adolescent with a 9.5/8.4/10.7 cm heterogeneous, hypoattenuating, symptomatic solid adnexal mass that resulted in being a degenerative uterine leiomyoma. Several other cases in the puerperal period, in perimenopause or even in postmenopause have been reported [18,26].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment aims to stop the bleeding and to preserve the uterus, if possible, especially in young women. Myomectomy was reported in 56% of cases (for details see table I); in the rest of the cases, a hysterectomy was performed [11,15,[17][18][19][22][23][24]. In only two cases, uterine artery embolization was the first line of treatment for patient hemodynamic stabilization followed by a hysterectomy [17].…”
Section: Discussionmentioning
confidence: 99%
“…While haemoperitoneum in association with rupture of a vessel overlying the fibroid is well-described in the literature, to our knowledge only seven other cases of rupture of a degenerated fibroid have been described in the literature [1][2][3][4][5][6][7]. All cases presented with abdominal pain, distension or symptoms of cardiovascular compromise.…”
Section: Michaela Weingarten [ 1 1 _ T D $ D I F F ] [ 1 0 _ T D $ D mentioning
confidence: 99%
“…The preoperative diagnosis was usually acute abdomen of uncertain cause, or acute adnexal pathology. In five of these eight cases [2,[4][5][6], a hysterectomy was performed at the time of the diagnostic operation. All patients recovered after their surgery.…”
Section: Michaela Weingarten [ 1 1 _ T D $ D I F F ] [ 1 0 _ T D $ D mentioning
confidence: 99%